Active learning in robotics based on simulation tools. Issue 3 (17th September 2011) - López‐Nicolás, G.; Romeo, A.; Guerrero, J. J.
Abstract Simulation is a powerful tool that has a very important role in the different areas of research, development, and education. In particular, simulation tools are widely used in robotics. In this article, we present an active learning experience based on simulation tools in the framework of robotics courses taught at engineering degrees. It is well known that the field of robotics involves many disciplines taught in higher education, such as mechanics, electronics, or computer science. In the context of a robotics course for an Industrial Engineering Masters degree, the different topics addressed can benefit from the use of simulation tools. Additionally, the benefits of active learning activities have been widely acknowledged and discussed. The main contribution of this work is the simulation tools fully integrated in the project‐based activity designed. Thus, one of the contributions is the software provided, developed with a clear teaching focus, and the successful teaching experience with a high academic level thanks in part to the simulation tools. Here, we describe the methodology and the new simulation tools, RobotScene and SGRobot, developed for this project‐based learning activity. This activity has been carried out successfully for several years; and our experience is that it motivates the students and improves their understanding of the theoretical concepts involved. We also present the academic results that support the benefits of the activity presented. © 2011 Wiley Periodicals, Inc. Comput Appl Eng Educ 22:509–515, 2014; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.10.1002/cae.20576